2020
DOI: 10.1371/journal.pone.0237952
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light irradiation on essential oil biosynthesis in the medicinal plant Asarum heterotropoides Fr. Schmidt var. mandshuricum (Maxim) Kitag

Abstract: Asarum heterotropoides Fr. var. mandshuricum (Maxim) Kitag (Chinese wild ginger) is an important medicinal herb. Essential oil extracted from its roots is the key ingredient and is mainly composed of phenylpropanoid compounds. As a skiophyte plant, light is a crucial factor for A. heterotropoides var. mandshuricum growth and metabolism. To investigate the effects of light irradiation on the essential oil biosynthesis in A. heterotropoides var. mandshuricum, the plants were cultivated in four light irradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The determination of essential oil-related precursors, i.e., phenylalanine, cinnamic acid, and shikimic acid, was carried out using an ultra-performance liquid chromatography system (Waters Acquity UPLC, Milford, Worcester County, MA, USA) coupled with a quadrupole mass spectrometer (Waters Xevo TQ, Milford, Worcester County, MA, USA) equipped with an ESI source, according to the methods that were previously described by Wang et al [18]. As well as the evaluation of the key enzyme activities involved in essential oil biosynthesis, including L-phenylalanine aminolyase, 3-deoxy-D-arabino-heptulosonate-7-phosphate synthase (DAHPS) and O-methyltransferase [18].…”
Section: Determination Of Essential Oil Levels and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of essential oil-related precursors, i.e., phenylalanine, cinnamic acid, and shikimic acid, was carried out using an ultra-performance liquid chromatography system (Waters Acquity UPLC, Milford, Worcester County, MA, USA) coupled with a quadrupole mass spectrometer (Waters Xevo TQ, Milford, Worcester County, MA, USA) equipped with an ESI source, according to the methods that were previously described by Wang et al [18]. As well as the evaluation of the key enzyme activities involved in essential oil biosynthesis, including L-phenylalanine aminolyase, 3-deoxy-D-arabino-heptulosonate-7-phosphate synthase (DAHPS) and O-methyltransferase [18].…”
Section: Determination Of Essential Oil Levels and Metabolismmentioning
confidence: 99%
“…Essential oils also are mainly composed of phenylpropanoid compounds, whereas cinnamic acid and p-coumaric acid have been important secondary metabolites in essential oil biosynthesis in plants [18]. Phenylpropanoid compounds are biosynthesized from phenylalanine via shikimic and cinnamic acids [34].…”
Section: Reduced Essential Oil Content and Metabolism By Maturation As Mitigated By Ecomentioning
confidence: 99%
“…respectively When compared with the rest of treatments. Wang et al, 2020 observed that the essential oil yield was proportional to the light irradiation the highest oil yield (1.86%) was obtained in plants grown in 100% full sunlight, while the lowest oil yield (1.30%) was obtained from plants grown in 12% full sunlight.…”
Section: Essential Oilmentioning
confidence: 94%
“…All pots were then placed at Medicinal Herbs Garden of Jilin Agricultural University (43.80′N, 125.42′E) under normal growing condition. In the next year, soon after the leaves appeared (second week of May 2019), we subjected the plants to different light treatments for 21 days; it is the time when A. heterotropoides leaves expand and it is known that the diurnal net photosynthetic rate increases when grown under variable light conditions [ 38 ]. The daytime temperature during 21 days treatment was 27.4–31 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Efforts have been made to optimize the extraction of volatile oil from this medicinally important plant [ 37 ]. The possible ways to increase the volatile oil production are 1) to understand the effect of different light intensities on the photosynthate and in turn on the volatile oil biosynthesis [ 38 ], 2) understand the volatile oil and its components’ biosynthesis-related pathways, and based on this knowledge, 3) develop high volatile oil yielding A. heterotropoides genotypes for large scale extraction. In this study, transcriptome sequencing of Asarum leaves grown under four different light treatments was performed to uncover the effect of light treatments on genes involved in pathways associated with the biosynthesis of methyleugenol, myristicin, safrole, and 3,5-dimethoxytoluene.…”
Section: Introductionmentioning
confidence: 99%